Unveiling the role of entrepreneurship education on green entrepreneurial intentions among business students: gender as a moderator - Victoria Makuya; Ismail Abdi Changalima (Cogent Education, 2024)
AbstractThe research investigates the impact of entrepreneurship education (EE) on green entrepreneurial intentions (GEI) among business students. Additionally, the study conducted a moderation analysis to examine whether gender influences the relationship between EE and GEI among female and male business students. Data were collected from 204 Tanzanian business students who had completed an entrepreneurship course as part of their major, using structured questionnaires. Quantitative data analysis and moderation effect testing were performed using PLS-SEM in SmartPLS 4. The findings reveal a significant positive relationship between EE and GEI. Moreover, gender was found to be significantly related to GEI, with males exhibiting a stronger effect compared to females. However, despite this, the study found that gender does not moderate the relationship between EE and GEI. This study offers unique insights into the influence of EE on GEI and the moderating effect of gender in the Tanzanian context. Furthermore, the study contributes to Sustainable Development Goal 4 by addressing the importance of enhancing education quality and ensuring inclusive and equitable learning opportunities for all individuals. The research also carries policy implications for promoting green business initiatives among future entrepreneurs. While the study provides valuable contributions, it is limited by its sample size, which solely consists of business students from Tanzania. Future research should consider expanding the sample to include students from various academic programs and diverse geographical locations to enhance the generalizability of the findings.